Elevated Asprosin Levels in Breast Cancer: Insights from a Comparative Study - Yur, Mesut; Ozcan, Sibel; Yildirim, Nilgun; Ozdede, Mehmet R.; Ozcan, Mete (Mary Ann Liebert, Inc, 2024)
Background: Breast cancer (BC) is the most common type of cancer in women. Diagnosis in the early stage is very important for cancer treatment. There is no good biomarker to diagnose BC in T1-T2 or N0 stage. This study aimed to evaluate asprosin (ASP) levels of BC compared with non-cancer.Materials and Methods: An enzyme-linked immunosorbent assay was used to evaluate serum ASP levels in 40 patients with BC and 40 healthy women. The cancer group included T1-T4, N1-N3, and M0-M1 patients. T stages were divided into groups as T1-T2 and T3-T4. N stages were divided into groups as N (0) and N (+).Results: ASP showed good discrimination (area under the curve = 0.767, 95% confidence interval: 0.657-0.878) between the BC group and the healthy group and acceptable discriminating ability (sensitivity = 0.825; specificity = 0.750) at the optimal cutoff value of 1.82 ng/mL. ASP indicated no difference for T, N, and M stages (p = 0.919, p = 0.859, and p = 0.225, respectively). There was a significant difference between grades within cancer patients in terms of ASP (p = 0.025).Conclusions: These findings provide evidence of a potential association between elevated ASP levels and the presence of BC. The observed higher levels of ASP in women with BC compared with healthy individuals suggest that ASP could potentially serve as a biomarker for distinguishing between the two groups. These results may contribute to our understanding of the potential role of ASP in BC detection and highlight its potential as a diagnostic marker. Further studies are required to establish whether ASP can be used to diagnose BC.
Keywords: biomarker; asprosin; adipokine; diagnosis